Selfies to die for: A review of research on self-photography associated with injury/death in tourism and recreation. (January 2021) - Weiler, Betty; Gstaettner, Anna M.; Scherrer, Pascal
Abstract: This paper reviews empirical research on the extent and nature of risks associated with dangerous tourist self-photography (selfies) and management responses. Global epidemiological studies have captured the extent of the problem, with studies recording 250+ media-reported deaths within the past decade. Nearly half occurred in natural environments, with key hazards being cliff edges, waterbodies, and wildlife. Researchers exploring the nature of the phenomenon identify contextual factors along with technology-induced distractions, as risk factors in selfie-taking. Demographics also feature, with the majority of casualties being young males. The literature points to management responses that relate to either the social or the risky nature of the phenomenon. The most prevalent are communication-related, ranging from education and awareness-raising to persuasive communication. Targeted communications that invoke social norms and innovative media are suggested for addressing the problem. Highlights: Selfie injuries and deaths are more common among young males. Cliff edges, water bodies and wildlife are key contextual factors. Sharing on social media and identity-creation are motivating factors. Targeted communication has the greatest likelihood of reducing adverse outcomes.